Electrodeposition NiMoSe ternary nanoshperes on nickel foam as bifunctional electrocatalyst for urea electrolysis and hydrogen evolution reaction. (3rd November 2021) - Wang, Haitao; Jiao, Xin; Zeng, Wenlu; Zhang, Ying; Jiao, Yongli
Abstract: Electrodeposition provides a simple but effective way to prepare advanced electrode for the application in electrochemical field. In this work, NiMoSe ternary nanospheres were deposited on nickel foam (NiMoSe/NF) by one-step electrodeposition. The morphology, phase and chemical composition of the electrode was characterized by using SEM, TEM, XRD and XPS. The electrode exhibited excellent performance for both urea oxidation reaction (UOR) and hydrogen evolution reaction (HER). It only required 1.39 V and 81 mV (vs. RHE) to deliver a current density of 10 mA/cm 2 for UOR and HER, respectively. The electrolyzer constructed with NiMoSe/NF as both anode and cathode could deliver a current density of 10 mA/cm 2 at a driving potential of 1.44 V. The stability test showed that the electrode had good durability as electrode for both UOR and HER. Considering the easiness, simplicity and low cost, the NiMoSe/NF electrode could find wide application in urea electrolysis. Graphical abstract: Image 1 Highlights: Ternary NiMoSe/NF electrocatalyst prepared by simple electrodeposition method. NiMoSe/NF exhibits excellent electrocatalytic activity for both UOR and HER. NiMoSe/NF electrode demonstrates good stability for urea electrolysis. The electrochemical conversion process provides potentiality for HER via treatment of urea-rich wastewater